Emerging Roles of Repetitive and Repeat-Containing RNA in Nuclear and Chromatin Organization and Gene Expression - Trigiante, Giuseppe; Blanes Ruiz, Nerea; Cerase, Andrea (Frontiers in Cell and Developmental Biology, 2021)
Genomic repeats have been intensely studied as regulatory elements, controlling gene transcription, splicing and genome architecture. Our understanding of the role of the repetitive RNA such as the RNA coming from genomic repeats, or repetitive sequences embedded in mRNA/lncRNAs, in nuclear and cellular functions is instead still limited. In this review we discuss evidence supporting the multifaceted roles of repetitive RNA and RNA binding proteins in nuclear organization, gene regulation, and in the formation of dynamic membrane-less aggregates. We hope that our review will further stimulate research in the consolidating field of repetitive RNA biology.